Recursos da tecnologia da informação e comunicação no ensino da estatística: o GeoGebra. - Souza, Ricardo Fernando de (2019)
This study demonstrates an analysis of the use of information and communication technology resources in the teaching of statistics for third year high school students from a private institution in the state of São Paulo. In this sense, a didactic sequence was elaborated and analyzed that included GeoGebra software to perform activities in the teaching and learning of descriptive statistics. The researcher's experience as a teacher found that students demonstrate difficulties in interpreting statements and manipulating algebraic equations for solving mathematical problems, as well as questioning the possibility of differentiated classes. As young people, they live in a universe flooded by TIC’s resources, making it necessary to understand the pedagogical possibilities of these resources. The study was based on Ausubel's theory, which systematized the conditions of teaching organization to promote meaningful learning in school education. The organized didactic sequence is based on the critical analysis of the contents proposed for high school through the documents that guide the teachers, such as the PCN´s and the reflections on the possible contributions of ICT`s as pedagogical tools. The research is characterized as a case study, with eight students of the third year of high school as participants. An initial and final evaluation was elaborated to verify the efficiency of the didactic sequence that happened in six meetings. The research data showed that students in this stage of schooling present inadequate appropriation of statistical concepts foreseen for the final years of elementary school II. The didactic sequence involving GeoGebra demonstrated the broadening of the understanding of descriptive statistics concepts also provided for high school, an easily manipulated software used at all levels of education.